The effectiveness of GaMaKe Media to train creative thinking in early childhood - Ningrum, Mallevi; Afifah Rahmaningrum; Melia Dwi Widayanti; Adhe, Kartika Rinakit (Universitas Nahdlatul Ulama Surabaya, 2025)
Creative thinking (CrTS) is one of the most important skills in the era of Society 5.0. The disparities that occur in creative thinking indicators are often experienced by children from an early age, especially in the indicators of originality and elaboration. This study aimed to test the GaMaKe (Firefighter Game) media as a solution to train indicators of CrTS in early childhood. GaMaKe media integrates game elements with fire disaster mitigation-based activities to provide meaningful experiences for early childhood. This research method uses a pre-experimental design with a one-group pre-test and post-test design with 54 children divided into three groups. The research results show that GaMaKe media can improve creative thinking in early childhood, showing significant results; the average N-Gain for class A is .53, class B is .57, and class C is .62, which is categorized as moderate; and there is no difference in the average N-Gain score through statistical testing of the Paired Sample T-test.